The implementation of mobile learning in Primary Schools in Indonesia - Alda Rizqy Amalia; Agus Wedi; Punaji Setyosari (Italian Journal of Educational Technology)
This research explores the implementation of mobile learning in primary schools in Indonesia through a systematic literature review (SLR). Following the systematic review methodology outlined by Newman and Gough (2020), this research conducted an analysis of selected articles. These articles were retrieved from Google Scholar to ensure a broad and relevant selection of sources. Most articles were published in 2021 and 2022. Mobile learning has become a significant trend in education, with its applications including videos, teaching materials, e-modules, augmented reality apps and applications for gadgets (applications that can be accessed through devices such as smartphones or tablets). Based on the results of this study, mobile learning has been successfully implemented in various subjects, demonstrating its potential to improve educational outcomes. However, significant challenges remain, including limited infrastructure, lack of teacher skills and inequitable access to digital devices. Challenges were also identified, such as teacher preparedness and accessibility for students.